2018
DOI: 10.1177/0268355517750523
|View full text |Cite
|
Sign up to set email alerts
|

Surgical methods and clinical results of subfascial endoscopic perforator surgery in Japan

Abstract: These results indicate that subfascial endoscopic perforator surgery is an alternative to improve the long-lasting disease severity and/or clinical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 33 publications
0
6
0
1
Order By: Relevance
“…Endovenous laser treatment (EVLT) is also one of the minimally invasive methods of endovenous treatment. The principle of treatment is to use the thermal effect released by the laser to damage the venous endothelium, damage the vein wall, and deposit thrombosis to occlude the varicose vein, which in turn obliterates the vena cava [ 9 , 10 ]. At present, most patients in clinical practice generally require combined treatment due to etiology, symptoms, severity, and other reasons.…”
Section: Introductionmentioning
confidence: 99%
“…Endovenous laser treatment (EVLT) is also one of the minimally invasive methods of endovenous treatment. The principle of treatment is to use the thermal effect released by the laser to damage the venous endothelium, damage the vein wall, and deposit thrombosis to occlude the varicose vein, which in turn obliterates the vena cava [ 9 , 10 ]. At present, most patients in clinical practice generally require combined treatment due to etiology, symptoms, severity, and other reasons.…”
Section: Introductionmentioning
confidence: 99%
“…9 Gonza´lez et al designed a noninferiority study between RF, HLS and conservative hemodynamic cure on 225 subjects. 12 RF was found 15 Primary VLU healing rate was reported as 96.2%, with a 12% recurrence rate. SEPS significantly decreased VCSSs from 10.0 � 6.6 to 3.1 � 3.4.…”
Section: Discussionmentioning
confidence: 92%
“…evaluated 1287 limbs of 1091 subjects that underwent SEPS (average follow-up was 47.7 months). 15 Primary VLU healing rate was reported as 96.2%, with a 12% recurrence rate. SEPS significantly decreased VCSSs from 10.0 ± 6.6 to 3.1 ± 3.4.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, Dodd (UIP name 1) : perforating veins of the femoral canal, 5.1.1) and Boyd perforators (UIP name: paratibial perforator veins, 3.1.1) are considered clinically significant because of their association with the great saphenous veins, and Cockett perforators (UIP name: posterior tibial perforator veins, 3.1.2) are considered clinically significant because of their association with lower leg stasis skin lesions. 2) In addition to direct ligation and resection, 3,4) subfascial endoscopic perforator surgery [5][6][7] and endovascular ablation, 8) sclerotherapy, 9) and glue treatment, 10) which are covered by insurance in Japan, have been reported for these typical perforator refluxes. On the contrary, approximately 90 perforator branches in the lower extremities have been reported, 11) and although atypical IPVs have not gained attention, some reports have analyzed the results of vein echocardiography as part of the pathophysiology referred to as nonsaphenous superficial vein (NSV) reflux, varicose veins without truncal saphenous reflux, and varicose veins with competent saphenous trunks, and it has been suggested that observing not only saphenous veins but also other veins and not overlooking the findings are essential for the accurate treatment of lower extremity varicose veins.…”
Section: Discussionmentioning
confidence: 99%